Model and data engineering : 8th International Conference, MEDI 2018, Marrakesh, Morocco, October 24-26, 2018, Proceedings /: 8th International Conference, MEDI 2018, Marrakesh, Morocco, October 24-26, 2018, Proceedings. (2018) - Unknown
No abstract available